2008
DOI: 10.1002/adma.200702781
|View full text |Cite
|
Sign up to set email alerts
|

Aerogel Templated ZnO Dye‐Sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSSCs) based on nanocrystalline TiO 2 have exhibited solar energy-conversion efficiencies of over 10% and remain one of the most promising candidates for cost-effective solar energy conversion devices. [1,2] The most efficient DSSCs reported to date utilize a high surface area photoanode, which allows for good light harvesting with a moderate extinction dye, in contact with the I 3 À /I À couple which acts as a redox mediator.[3] The good performance of DSSCs is partially attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 25 publications
1
118
0
Order By: Relevance
“…[33][34][35] Also, because ALD is not a line-of-sight technique, it can be used to make nanostructured 'thin films' which are prepared in an identical fashion to the model thin films, but have increased light absorption. [36][37][38] Thus lessons learned with our thin film model system can be directly applied to nanostructured architectures with precisely controlled dimensions fabricated via ALD.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Also, because ALD is not a line-of-sight technique, it can be used to make nanostructured 'thin films' which are prepared in an identical fashion to the model thin films, but have increased light absorption. [36][37][38] Thus lessons learned with our thin film model system can be directly applied to nanostructured architectures with precisely controlled dimensions fabricated via ALD.…”
Section: Introductionmentioning
confidence: 99%
“…4,[10][11][12][13] Access to these architectures has been facilitated by several attractive fabrication strategies, among them (a) surfactant-controlled crystallization, 10,14 (b) controlled film corrosion, 15 and (c) templated atomic-layer deposition (ALD). 11,[16][17][18][19][20][21][22][23][24] Pseudo 1-D nanostructures, particularly with single or polycrystalline domains, are especially interesting since electrons traveling through the nanoparticle semiconductors are believed to move under diffusive control. 25 Here we quantify the characteristic conductivity and capacitance of the photoanodes, Figure 1, in assembled ZnO nanotube DSCs via electrochemical impedance spectroscopy (EIS).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to conventional channel plates, aerogel-templated materials have larger open area ratios, larger surface areas, and are relatively easy to fabricate in large flat form factors. We have already demonstrated that aerogels can both be functionalized and work well as photo-anodes for solar cells [58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: E Aerogel Substratesmentioning
confidence: 99%